Civil Rights and the Environment in African-American Literature, 1895-1941 - Claborn, John (Environmental Cultures, 2017)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The beginning of the 20th century marked a new phase of the battle for civil rights in America. But many of the era's most important African-American writers were also acutely aware of the importance of environmental justice to the struggle. Civil Rights and the Environment in African-American Literature is the first book to explore the centrality of environmental problems to writing from the civil rights movement in the early decades of the century. Bringing ecocritical perspectives to bear on the work of such important writers as Booker T. Washington, W.E.B. Du Bois, the writers of the Harlem Renaissance and Depression-era African-American writing, the book brings to light a vital new perspective on ecocriticism and modern American literary history.